2000
DOI: 10.1002/1099-0984(200007/08)14:4<291::aid-per377>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The multicultural personality questionnaire: a multidimensional instrument of multicultural effectiveness

Abstract: In today's global business environment, executive work is becoming more international in orientation. Several skills and traits may underlie executive success in an international environment. The Multicultural Personality Questionnaire was developed as a multidimensional instrument aimed at measuring multicultural effectiveness. The questionnaire has scales for Cultural Empathy, Openmindedness, Emotional Stability, Orientation to Action, Adventurousness/Curiosity, Flexibility, and Extraversion. In a study amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
289
6
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 480 publications
(374 citation statements)
references
References 28 publications
20
289
6
16
Order By: Relevance
“…The Multicultural Personality Questionnaire (MPQ, Van der Zee & Van Oudenhoven, 2000;2001) was developed to assess five traits that are key to individuals' cultural adaptability and their psychological well-being in a foreign environment. It was developed as the need arose among cross-cultural psychologists to have a questionnaire that was more sensitive to contextual variables (Van der Zee & Van Oudenhoven, 2000;2001).…”
Section: The Multicultural Personality Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…The Multicultural Personality Questionnaire (MPQ, Van der Zee & Van Oudenhoven, 2000;2001) was developed to assess five traits that are key to individuals' cultural adaptability and their psychological well-being in a foreign environment. It was developed as the need arose among cross-cultural psychologists to have a questionnaire that was more sensitive to contextual variables (Van der Zee & Van Oudenhoven, 2000;2001).…”
Section: The Multicultural Personality Questionnairementioning
confidence: 99%
“…It was developed as the need arose among cross-cultural psychologists to have a questionnaire that was more sensitive to contextual variables (Van der Zee & Van Oudenhoven, 2000;2001). The authors felt that the standard Big Five inventories lacked measures "specifically tailored to grasp individual differences predictive of multicultural attitudes and multicultural success" (Leone, Van der Zee, Van Oudenhoven, Perugini, & Ercolani, 2005, p. 1450.…”
Section: The Multicultural Personality Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis of the set of characteristics pointed out by several authors and previous studies, Van der Zee and Van Oudenhoven (2000) have identified a number of specific personality characteristics, grouping them into five dimensions of multicultural competence. The structure of personality arises from its various dimensions (dispositional factors that continuously determine personality), which are the result of grouping personality traits together (Almiro & Simões, 2010.…”
Section: Multicultural Personality (Mp)mentioning
confidence: 99%
“…Elements of flexibility, such as the ability to learn from mistakes and new experiences, are crucial for multicultural effectiveness (Sousa, Gonçalves, & Cunha, 2015;Spreitzer, McCall, & Mahoney, 1997). The fifth dimension, social initiative, includes an attitude of openness to new cultures, a predisposition to seek and explore new situations, facing them as challenges, and the ability to establish and maintain contacts easily (Van der Zee & Van Oudenhoven, 2000. These dimensions are positively associated with extroversion, satisfaction with life, work productivity, openness to new experiences, international orientation, social adjustment, job satisfaction, and negatively associated with hostility, neuroticism and social anxiety (e.g., Ali, Van der Zee, & Sanders, 2003;Leong, 2007).…”
Section: Multicultural Personality (Mp)mentioning
confidence: 99%